2017
DOI: 10.14379/iodp.sp.381.2017
|View full text |Cite
|
Sign up to set email alerts
|

Expedition 381 Scientific Prospectus: Corinth Active Rift Development

Abstract: Continental rifting is fundamental for the formation of ocean basins, and active rift zones are dynamic regions of high geohazard potential. However, much of what we know from the fault to plate scale is poorly constrained and is not resolved at any level of spatial or temporal detail over a complete rift system. For International Ocean Discovery Program Expedition 381, we propose drilling within the active Corinth rift, Greece, where deformation rates are high, the synrift succession is preserved and accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 86 publications
2
14
0
Order By: Relevance
“…Our research indicates the CFS initiated at ∼0.6 Ma in the eastern portion of the rift. This time of fault initiation aligns with a growing body of literature pinning down the onset of the rapid and localized Middle Pleistocene rifting in Corinth (e.g., de Gelder et al., 2019; McNeill et al., 2019; Nixon et al., 2016). Still, further research and new data sets are needed to provide additional constraints in westward portions of the rift margin.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our research indicates the CFS initiated at ∼0.6 Ma in the eastern portion of the rift. This time of fault initiation aligns with a growing body of literature pinning down the onset of the rapid and localized Middle Pleistocene rifting in Corinth (e.g., de Gelder et al., 2019; McNeill et al., 2019; Nixon et al., 2016). Still, further research and new data sets are needed to provide additional constraints in westward portions of the rift margin.…”
Section: Discussionsupporting
confidence: 83%
“…(1996) also recovered a rigid layer thickness of ∼10 km, which translates into a T e between 2.0 and 2.5 km, in line with our determination (Table 3). The offshore sedimentary record in the hanging wall, both from cores and geophysics, suggests similarly rapid slip rates and flexural wavelengths (de Gelder et al., 2019; McNeill et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similar extensional processes and related sedimentary deposits characterize other complex multi-plate regions such as the Caribbean (Driscoll & Diebold, 1999; Escalona & Mann, 2011) and Indonesia, for example Kalimantan Basins, Borneo (Van de Weerd & Armin, 1992; Hall, 2002). Acquiring additional information on the deep sedimentary fill of marine extensional basins requires deep-sea drilling, as recently achieved for the Gulf of Corinth (Greece) (McNeill, Shillington & Carter, 2017) during October–December 2017, together with ongoing onshore studies (January 2018 onwards).…”
Section: Introductionmentioning
confidence: 99%
“…From October to December 2017 International Ocean Discovery Program (IODP) Expedition 381 drilled the uppermost (~800 m) part of the offshore syn-rift sedimentary sequence of the Corinth rift basin at four holes from the central and eastern part of the Gulf of Corinth (McNeill et al, 2019b) (Figure 1), providing a unique continuous and intact sedimentary archive to study the evolution of this young rift basin in high detail. The study of these cores, presented by (McNeill et al 2019a;2019b) revealed that the initial connection of the Corinth basin to the global oceans was preceded by several marine incursions controlled by eustatic sea level fluctuation during glacial-interglacial cycles. This caused a cyclic shift in basin paleoenvironment from marine to lacustrine, which in turn affected sediment supply (i.e., higher sedimentation rates during lacustrine/lowstand periods, and lower sedimentation rates during marine/highstand periods), and lithology (McNeill et al 2019a;2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The study of these cores, presented by (McNeill et al 2019a;2019b) revealed that the initial connection of the Corinth basin to the global oceans was preceded by several marine incursions controlled by eustatic sea level fluctuation during glacial-interglacial cycles. This caused a cyclic shift in basin paleoenvironment from marine to lacustrine, which in turn affected sediment supply (i.e., higher sedimentation rates during lacustrine/lowstand periods, and lower sedimentation rates during marine/highstand periods), and lithology (McNeill et al 2019a;2019b). Higher sediment supply during glacials has also been documented from the onshore syn-rift sequence at the southern margin of the Corinth basin by Cullen et al (2021).…”
Section: Introductionmentioning
confidence: 99%